1997
DOI: 10.2105/ajph.87.10.1626
|View full text |Cite
|
Sign up to set email alerts
|

Prescription drug spending: the impact of age and chronic disease status.

Abstract: OBJECTIVES: The purpose of this study was to examine how pharmaceutical expenditures vary by age and the presence of chronic health problems. METHODS: Data from the 1987 National Medical Expenditure Survey were used to obtain nationally representative estimates of outpatient prescription drug expenditures for the noninstitutionalized population and the fraction of total health expenditures used to purchase medications for age-chronic disease population subgroups. RESULTS: Although the elderly make up 12% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
52
2
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 7 publications
3
52
2
5
Order By: Relevance
“…Third party payments covered only 81% of that total with the remaining $172.4 billion being paid out-of-pocket by consumers (U.S. Bureau of the Census 1998). Research has shown that these out-of-pocket health care expenditures increase with age (Acs and Sabelhaus 1995;Cutler and Meara 1998;Hitschler 1993;Rubin and Koelln 1993) and chronic disease status (Mueller, Schur, and O'Connell 1997). Could these increases in outof-pocket health care expenditures associated with age and chronic disease status be a factor that contributes to the increased risk that a newly widowed individual will experience a substantial decline in needs-adjusted income?…”
Section: Out-of-pocket Medical Care Expendituresmentioning
confidence: 99%
“…Third party payments covered only 81% of that total with the remaining $172.4 billion being paid out-of-pocket by consumers (U.S. Bureau of the Census 1998). Research has shown that these out-of-pocket health care expenditures increase with age (Acs and Sabelhaus 1995;Cutler and Meara 1998;Hitschler 1993;Rubin and Koelln 1993) and chronic disease status (Mueller, Schur, and O'Connell 1997). Could these increases in outof-pocket health care expenditures associated with age and chronic disease status be a factor that contributes to the increased risk that a newly widowed individual will experience a substantial decline in needs-adjusted income?…”
Section: Out-of-pocket Medical Care Expendituresmentioning
confidence: 99%
“…A maioria dos estudos de utilização de medicamentos relata o uso de um número médio de quatro medicamentos por idoso 4,5,6,7,8,9 . O perfil de utilização de medicamentos por idosos acarreta em gasto elevado com a aquisição dos mesmos em comparação ao observado nas demais faixas etárias 10,11 .…”
Section: Introductionunclassified
“…A maioria dos estudos de utilização de medicamentos relata o uso de um número médio de quatro medicamentos por idoso 4,5,6,7,8,9 . O perfil de utilização de medicamentos por idosos acarreta em gasto elevado com a aquisição dos mesmos em comparação ao observado nas demais faixas etárias 10,11 .Os gastos com medicamentos utilizados pelos idosos são concentrados em determinadas categorias terapêuticas. Considerando o primeiro nível de classificação Anatomical Therapeutical Chemical (ATC) 12 dos medicamentos, as categorias sistema cardiovascular, sistema nervoso e trato alimentar e metabolismo são responsáveis pela maior parte dos gastos por idosos 13,14,15 .…”
unclassified
“…Multiple morbidity often increases older adults' economic vulnerability (Mueller, Schur, & O'Connell, 1997;Bierman & Clancy, 2000;Crystal, Johnson, Harman, Sambamoorthiu, & Kumar, 2000;Stroupe, Kinney, & Knieser, 2000;Tu, 2004). Because those individuals who endure the greatest frequency of multiple morbidities tend to be those with the fewest financial resources, multiple morbidity can pose a significant burden to older adults with lower incomes.…”
mentioning
confidence: 99%